2018
DOI: 10.1155/2018/9329123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biochemical and Densitometric Markers of Calcium-Phosphate Metabolism in the Groups of Patients with Multiple Sclerosis Selected due to the Serum Level of Vitamin D3

Abstract: Background In addition to the widely known effect of vitamin D3 (vitD3) on the skeleton, its role in the regulation of the immune response was also confirmed. Aim The assessment of biochemical and densitometric markers of calcium-phosphate metabolism in the groups of patients with relapsing-remitting multiple sclerosis (RRMS) selected due to the serum level of vitamin D3. Methods The concentrations of biochemical markers and indices of lumbar spine bone densitometry (DXA) were determined in 82 patients divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Lastly, EDSS scores were comparable between male and female MS patients, which is consistent with previous research [86,87]. In female MS patients, however, EDSS showed negative correlations with free and bioavailable 1.25(OH) 2 D; free, bioavailable, and total 25(OH)D; and 24.25(OH) 2 D, which is in line with earlier studies, which reported a negative correlation between EDSS and 1.25(OH) 2 D or 25(OH)D, respectively [46,88]. In contrast, in male MS patients, negative correlations between EDSS and CTX, P1NP, and osteocalcin were observed, which differs from previous studies, which found no correlations between EDSS and BTMs or only a positive correlation between EDSS and CTX [67,89].…”
Section: Discussionsupporting
confidence: 85%
“…Lastly, EDSS scores were comparable between male and female MS patients, which is consistent with previous research [86,87]. In female MS patients, however, EDSS showed negative correlations with free and bioavailable 1.25(OH) 2 D; free, bioavailable, and total 25(OH)D; and 24.25(OH) 2 D, which is in line with earlier studies, which reported a negative correlation between EDSS and 1.25(OH) 2 D or 25(OH)D, respectively [46,88]. In contrast, in male MS patients, negative correlations between EDSS and CTX, P1NP, and osteocalcin were observed, which differs from previous studies, which found no correlations between EDSS and BTMs or only a positive correlation between EDSS and CTX [67,89].…”
Section: Discussionsupporting
confidence: 85%
“…The relation between 25-OHD3 and inflammation risk was studied by most researchers [14], while others assessed the role of 25-OHD3 in myelination and re-myelination [15]. Thus, 25-OHvitD3 has vital roles in CNS functions, maturement of the immune cells, homeostasis of epithelial barrier and inhibiting proliferation and induces differentiation for different type of cells [16]. Also, the blood homeostasis for both calcium and phosphate is maintained via vitamin D with the PTH [17] Typically, neurologists have assessed MS patient disability by "Expanded Disability Status Scale" (EDSS).…”
Section: Introductionmentioning
confidence: 99%